The Biblical Roots of Locke's Theory of Personal Identity - Lucci, Diego (Zygon, 2021)
Locke's consciousness-based theory of personal identity resulted not only from his agnosticism on substance, but also from his biblical theology. This theory was intended to complement and sustain Locke's moral and theological commitments to a system of otherworldly rewards and sanctions as revealed in Scripture. Moreover, he inferred mortalist ideas from the Bible, rejecting the resurrection of the same body and maintaining that the soul dies at physical death and will be resurrected by divine miracle. Accordingly, personal identity is neither in the soul, nor in the body, nor in a union of soul and body. To Locke, personal identity is in consciousness, which, extending “backwards to any past Action or Thought,” enables the self, both in this life and upon resurrection for the Last Judgment, to recognize that “it is the same self now it was then; and ‘tis by the same self with this present one that now reflects on it, that that Action was done” (Essay II.xxvii.9).